On Approximate Euler Differential Equations. (12th October 2009) - Jung, Soon-Mo; Min, Seungwook
Abstract : We solve the inhomogeneous Euler differential equations of the formx 2 y ′ ′ ( x ) + α x y ′ ( x ) + β y ( x ) = ∑ m = 0 ∞ a m x m and apply this result to the approximation of analytic functions of a special type by the solutions of Euler differential equations.